1998
DOI: 10.1038/bjc.1998.517
|View full text |Cite
|
Sign up to set email alerts
|

Truncated midkine as a marker of diagnosis and detection of nodal metastases in gastrointestinal carcinomas

Abstract: Midkine (MK) is a growth factor identified as a product of a retinoic acid-responsive gene. A truncated form of MK mRNA, which lacks a sequence encoding the N-terminally located domain, was recently found in cancer cells. We investigated the expression of the truncated MK mRNA in specimens of 47 surgically removed human gastrointestinal organs using polymerase chain reaction. Truncated MK was not detected in all of the 46 corresponding non-cancerous regions. On the other hand, this short MK mRNA was expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
(22 reference statements)
1
24
0
Order By: Relevance
“…Expression of a truncated form of MK (t-MK) mRNA, which lacks exon 3 encoding the N terminus, has been well documented in various tumours, including colon (Miyashiro et al, 1996), breast (Miyashiro et al, 1997), gastric (Aridome et al, 1998), and liver and kidney (Tao et al, 2007). Therefore, we immunostained OSCC tissues with IP-14 antibody, which had an epitope in the C-terminus, and IP-10 antibody, which had an epitope in the N-terminus.…”
Section: Ip-10mentioning
confidence: 99%
“…Expression of a truncated form of MK (t-MK) mRNA, which lacks exon 3 encoding the N terminus, has been well documented in various tumours, including colon (Miyashiro et al, 1996), breast (Miyashiro et al, 1997), gastric (Aridome et al, 1998), and liver and kidney (Tao et al, 2007). Therefore, we immunostained OSCC tissues with IP-14 antibody, which had an epitope in the C-terminus, and IP-10 antibody, which had an epitope in the N-terminus.…”
Section: Ip-10mentioning
confidence: 99%
“…In the last few years, MK was found to be overexpressed in various human malignant tumours. Northern blot experiments revealed MK mRNA expression in gastric cancers (Aridome et al, 1995(Aridome et al, , 1998, colorectal cancers (Aridome et al, 1995(Aridome et al, , 1998Ye et al, 1999), urinary bladder cancer (O'Brien et al, 1996), neuroblastoma (Nakagawara et al, 1995), Wilm's tumour (Tsutsui et al, 1993), and astrocytoma (Mishima et al, 1997). Interestingly, MK mRNA was reported to be extensively expressed in the early stage of colon cancer carcinogenesis (Ye et al, 1999).…”
mentioning
confidence: 99%
“…This conclusion agrees with reports about tMK expression in metastatic foci. 18 Our study showed that tMK expression is involved in tumor malignancy including resistance to anticancer agents. The expression of tMK may be a sign of malignancy and provide useful information for clinical chemotherapy.…”
Section: Discussionmentioning
confidence: 67%